Assessment of Visual Skills and Motor Performance of Soccer Players in Ethiopian Youth Sport Academy - Amare Sorate (Ph.D), Biruk (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2020)
The purpose of this study was to assess the visual skills and motor performance of soccer players in Ethiopian youth sport academy. Cross-sectional study design was used. From the available subjects 62 youth soccer players (28 male and 34 female) were participated using simple random sampling techniques. The primary sources of data such as demographic characteristics (age group, sex, and playing position), the visual skill tests (visual acuity, and color vision) and motor performance (eye hand coordination, eye foot coordination and reaction time) were measured. The results were presented as mean ± SD, Frequency proportions and figures was used to show the visual skill and motor performance status, Multivariate Roy’s Largest Root Tests was used to examine the impacts of visual skills on motor performance and ANOVA was used to see the difference of visual skills and motor performance in playing positions. Whereas, Pearson product moment correlation coefficient was used to test the relationship between visual skills and motor performance. Significance level was set at 0.05 levels for each of the statistical tests. SPSS version 20 software was used for all statistical analysis. The result indicates that color blindness and visual acuity status of the players independently and in group exercising couldn’t bring significant change on players motor performance. There was no difference between the playing positions of the player in color blindness, visual acuity, eye hand coordination and reaction time, while there was difference between playing positions in eye foot coordination. Color blindness test significantly and positively correlated with motor performance to reaction time. Visual acuity significantly and positively correlated with motor performance to eye hand coordination. Therefore, the Ethiopian youth sport academy and the concerned body should check the players visual skill as well as their motor performance and incorporate in selection criteria